Gastronomic sustainability: Use of by-products derived from the production chain of the Diacol Capiro potato variety (Revista Científica Ciencias Naturales y Ambientales, 2022)
The waste or by-products generated from food processing activities continue to grow and have a negative impact on the environment, this is due to the lack of strategies or properly managed resources, under this dynamic for several years the gastronomic industry seeks to support, that is why the need to involve practices around sustainability and innovation has been raised. This is how from the gastronomic exercise it is possible to contribute towards the mitigation of said problem, with the generation of new products and the use of new raw materials as a base in gastronomic preparations. In the present study, the objectives were to develop a use of the by-products derived from the productive chain of the potato variety Diacol Capiro and the response to the level of liking of these preparations was increased. For this, a standardization of flours and formulations of standard recipes was carried out. Subsequently, a sensory analysis was carried out using a hedonic scale from 1 to 9 points, using an internal panel without alteration of 70 people and evaluating attributes such as: flavor, color, aroma and texture, in four preparations. Similarly, in order to determine statistically significant differences in the level of liking for each attribute, an analysis of variance (p < 0.05) and a minimum significant difference test for comparison between the samples were performed. The results obtained reported that there are significant differences in the level of liking of all the samples in each attribute, determining that the preparation “Profiterol with Catalan cream and caramel” presented greater acceptability in the attributes of color, flavor and texture.
Keywords: Sustainability; Gastronomy; Use; By-products